Adopsi Website Desa dalam Transformasi Digital Pelayanan Publik: Studi Kasus Desa Margo Mulyo - Intan Permata Sari; Adityo Pratikno Ramadhan; Anita Marianata (PUBLICNESS: Journal of Public Administration Studies, 2025)
This study aims to analyze the utilization of village websites in improving public services in Margo Mulyo Village, Central Bengkulu. Using a qualitative case study approach, data were collected through interviews, observations, and documentation, and then analyzed with Miles and Huberman’s content analysis stages. The findings reveal that although the website is available, its use remains low due to limited digital literacy, unstable internet access, and people’s preference for direct services. The technology adoption process is still in the early stages according to the diffusion of innovation theory. Theoretically, this research contributes by enriching the discourse on digital transformation in rural public services and expanding the diffusion of innovation framework with socio-cultural factors. Practically, it provides recommendations for local governments and village officials to strengthen training, socialization, and infrastructure as a strategy for inclusive and sustainable digital governance in villages.